2018
DOI: 10.18632/oncotarget.25989
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib-based targeted therapy against pulmonary sarcomatoid carcinoma: a case report and literature review

Abstract: Sarcomatoid carcinoma is a rare malignancy characterized by a combination of epithelial and sarcoma or sarcoma-like components. In this study, we reported one case of pulmonary sarcomatoid carcinoma and evaluated the safety and efficacy of apatinib, a tyrosine kinase inhibitor selectively targeting vascular endothelial growth factor receptor 2, in treating this disease. The tumor mass was detected in the left lung of a 75-year-old man and showed positive immunostaining for cytokeratin (CK) 7, CK8, smooth muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…PD-L1 expression was noted in 44.4% and 12.0% of mutant and wild-type KRAS genes, respectively ( 21 ). Therapies targeting several genes, including EGFR-TKI ( 13 , 22 , 23 ), ALK-TKIs ( 24 ), MET-TKIs ( 25 ), antiangiogenic therapy ( 26 , 27 ) and immune-checkpoint inhibitors ( 21 , 28 ), were tested in patients with PSC, although given the rarity of the tumor type, large scale studies of any particular therapy may never be completed.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 expression was noted in 44.4% and 12.0% of mutant and wild-type KRAS genes, respectively ( 21 ). Therapies targeting several genes, including EGFR-TKI ( 13 , 22 , 23 ), ALK-TKIs ( 24 ), MET-TKIs ( 25 ), antiangiogenic therapy ( 26 , 27 ) and immune-checkpoint inhibitors ( 21 , 28 ), were tested in patients with PSC, although given the rarity of the tumor type, large scale studies of any particular therapy may never be completed.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, there were no evident complications associated with apatinib. 79 Li et al reported a case in which the patient was administered apatinib (250 mg) orally once per day. Sustained tumor regression was observed after treatment, and no severe complications were reported to be associated with apatinib therapy.…”
Section: Targeted Therapymentioning
confidence: 99%
“…According to the Li et al , one PSC patient treated with apatinib, a TKI that selectively targets VEGFR2 expression in tumor cells, showed sustained tumor regression after treatment. No severe complications are associated with apatinib therapy ( 24 ). Patients with post-operative recurrent PSC treated with anlotinib combined with chemotherapy (dacarbazine and cisplatin) have also achieved CR ( 25 ).…”
Section: Discussionmentioning
confidence: 99%